2010
DOI: 10.1515/znc-2010-3-412
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and β-Estradiol Stimulate Seed Germination in Chickpea by Causing Important Changes in Biochemical Parameters

Abstract: Effects of progesterone and β-estradiol on morphologic (germination velocity, root and shoot length) and biochemical (activities of α-amylase, superoxide dismutase, peroxidase and catalase, H2O2 content, lipid peroxidation) parameters during germination and post-germination stages of chickpea seeds were studied. The seeds germinated at various hormone concentrations (10 - 4, 10 - 6, 10 - 9, 10 - 12, 10 - 15 M) were harvested at the end of the 1st, 3rd, and 5th day. With comparison to the control, these hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 37 publications
1
31
0
1
Order By: Relevance
“…The studies demonstrated that exogenous application of mammalian sex hormones (such as β-estradiol, progesterone and androsterone) substantially improved plant growth and development, augmented protein and nucleic acid contents, stimulated oxidative enzyme activities, reduced H2O2 content, and the lipid peroxidation (MDA) level under non-stress conditions (Karl and Lauchli 2010;Erdal and Dumlupinar 2010). Also, MSHs also affected the inorganic constituents of plants (Erdal and Dumlupinar 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…The studies demonstrated that exogenous application of mammalian sex hormones (such as β-estradiol, progesterone and androsterone) substantially improved plant growth and development, augmented protein and nucleic acid contents, stimulated oxidative enzyme activities, reduced H2O2 content, and the lipid peroxidation (MDA) level under non-stress conditions (Karl and Lauchli 2010;Erdal and Dumlupinar 2010). Also, MSHs also affected the inorganic constituents of plants (Erdal and Dumlupinar 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in CAT and POX activity in Solanum melongena L might lead to accumulation of toxic amount of H 2 O 2 . Erdal and Dumlupinar (2010) demonstrated that progesterone stimulated antioxidant enzyme activities in germinating seeds of chickpea, maize and bean. Yeast used in the current study was tested to produce IAA with or without addition of tryptophan as precursor of IAA, their productivity increased with addition of tryptophan (Fig.…”
Section: Plant Growth and Biochemical Characterizationmentioning
confidence: 99%
“…These hormones were first detected in plants in the beginning of the nineteenth century [2]. Since then, although many studies have been made about presence, quantities and roles of these hormones in plants, their effect mechanisms have not been exactly elucidated, yet [1][2][3][4][5].…”
mentioning
confidence: 99%
“…Many researchers reported that it affected positively plant growth and development when MSH exogenously treated [1][2][3][4][5][6]. There are a lot of reports regarding effects of MSH on both morphological (seed germination, root and shoot lengths, dry and fresh weights) and biochemical (protein and sugar contents, amylase activity, oxidative enzyme activities, H 2 O 2 content, and lipid peroxidation level) parameters in plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation